Fostering Public Trust and Accountability in Public Healthcare: The Role of Transparency, Integrity, and Independence in Internal Audit Governance - Nasution, Fahmi Natigor; et al. (European Journal of Social Science Education and Research, 2026)
This study examines how transparency, independence, and integrity contribute to strengthening internal audit quality within public healthcare governance. Positioned within broader discussions of public trust, institutional accountability, and ethical governance in developing-country contexts, the study investigates the role of integrity as a moderating factor in the relationship between transparency, independence, and internal audit quality. Using a quantitative explanatory design, data were collected from 320 respondents across 36 public hospitals in North Sumatra Province, Indonesia, representing hospital directors, deputy directors, heads of finance, planning, medical services, supervision, and administrative units. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate both direct and moderating effects. The findings reveal that transparency and independence positively and significantly influence internal audit quality, indicating that accountable and autonomous oversight mechanisms are essential for strengthening governance effectiveness in public healthcare institutions. The study also finds that integrity does not moderate the relationship between transparency and audit quality, suggesting that transparency functions as an institutionalized governance mechanism independent of individual ethical characteristics. However, integrity significantly strengthens the relationship between independence and internal audit quality, highlighting the importance of ethical values in ensuring effective and trustworthy oversight. These findings contribute to broader social science discussions concerning institutional legitimacy, governance reform, and the delivery of accountable public welfare services in transitional and developing governance systems.